Quantificação das moléculas CD35/CR1, CD11b/CR3 em leucócitos de pacientes com leishmaniose visceral - Campelo, Cássio Marinho (2017)
Leishmaniasis is endemic in 98 countries worldwide. They are among the six most frequent infectious and parasitic diseases in the world, the second among those caused by protozoa after malaria. Visceral leishmaniasis is an anthropozoonosis of high incidence, morbidity and mortality in the Americas. In Brazil, Leishmaniainfantum has a wide distribution with notification in 20 states, among them Ceará. Type 1 (CR1) and type 3 (CR3) complement receptors are present on the surface of leukocytes acting on cell adhesion, in apoptotisis cell phagocytosis and on parasite interactions with host blood. The objective of this study was to understand the dynamics of CR1 and CR3 receptor expression in leukocytes in the blood of patients with visceral leishmaniasis. Peripheral blood samples from 18 patients with positive diagnosis for visceral leishmaniasis were analyzed conformed clinical, parasitological and serological aspects and 18 healthy individuals. neutrophils CD11b+CD35+ , CR3 expression decrease and neutrophil CD11b+CD14+CD35+ subpopulations, an increase in CR1 expression with decrease in the frequency of positive cells to the molecule were observed, suggesting a parasite tropism for this population and consequently a Escape route and silent entry in macrophages; In monocytes CD14+CD35+ were observed, an increase in CR1 expression with an increase of cells positive for the molecule, and in monocytes CD14+ CD11b+CD35+, there was an increase in the expression of CR3 and CR1 with an increase of the frequency of cells positive for the molecules, Suggesting that the monocyte is a target cell for the parasite and that the association of these receptors for complement may act to increase phagocytosis and modulate the differentiation of monocytes in anti-inflammatory macrophages; In B lymphocytes CD19+CD35+, a decrease of CR1 positive cells was observed, suggesting a possible action of complement receptor (CD35/CR1) on the physiological regulation of the polyclonal activation of these cells. The data demonstrated a significant statistic by the t test (p <0.05) and the results suggest that differences in the expression of CR1 and CR3 can be considered an important factor in the persistence of the parasite in the disease.